STRATEGI PEMASARAN UNTUK IKAN HIAS LAUT (MARINE) BERKELANJUTAN - Mauli Kasmi (JURNAL LENTERA BISNIS, 2023)
This research aimed to identify effective sustainable marketing strategies for marine ornamental fish. The research was conducted in South Sulawesi waters over a 6-month period, from September 2022 to March 2023. Primary data were obtained through interviews with fishermen groups and related parties, such as traders/collectors, TPI officers, and Marine and Fisheries Agency officers. The data included the condition of marketed products, fish marketing system, and description of marketing channels in South Sulawesi waters. The analysis method used is descriptive method. One of the indicators used to measure marketing efficiency is ornamental fish price data, by comparing the price received by producers/fishermen with the price paid by final consumers (farmers' share). The results of this research are expected to provide guidance in developing sustainable marketing strategies that can increase the economic value and sustainability of the marine ornamental fish industry. The implications of this research are also expected to contribute to efforts to conserve marine ornamental fish resources in Indonesia.,Â Key words: marine ornamental fish, marketing strategy, sustainability, South Sulawesi waters.